Mud film composition and preparation method thereof
Deep pore cleaning and application comfort in the prior art is solved by using mud film compositions in facial cleaning products, combining dispersants, film forming agents and specific ingredients such as zinc sulfate, supramolecular salicylic acid and red pine leaf extracts. The poor problem has achieved effective black and white head dredging and oil control effects.
Patent Information
- Application Number
- CN202411407305.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing facial cleaning products cannot penetrate deep into the pores while removing surface blackheads and dirt, resulting in repeated blackhead problems, poor application effect, easy to damage the skin, and difficult to clean.
Using a mud film composition, including phase A, phase B, phase C and phase D, the dispersion and uniformity of coating are improved by adding dispersing agents such as titanium dioxide and fluorogenic mica, and film forming agents such as plulandosaccharides are used to improve dispersion and coating uniformity. Reduce water evaporation and loss of small-molecular active substances, and add zinc sulfate to quickly shrink pores, combining supramolecular salicylic acid, PCA zinc and red pine leaf extract to achieve pore dredging, oil control, and bactericidal and antibacterial effects.
It has achieved a thorough cleaning of deep blackheads, improved the application comfort and cleaning ability, significantly reduced the recurrence of blackhead problems, and improved the delicateness of the skin and the comfort of use.
Smart Images

Figure CN119235720A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of skin care products, and in particular to a mud mask composition and a preparation method thereof. Background Art
[0002] Facial cleansing is the first and most important step in facial skin care. It removes oil, dirt, and stratum corneum from the face to avoid clogged pores, blackheads, and acne. Therefore, facial cleansing products are an important category of skin care products, maintaining stable and continuous growth every year. In 2023, it will increase by 2.5% and sales will reach RMB 24.849 billion.
[0003] There are many facial cleansing products on the market, and several common facial cleansing products have certain problems while achieving facial cleansing. For example, although daily facial cleansers can remove oil and dust on the surface of the skin, they cannot penetrate deep into the pores to clean blackheads and whiteheads; although tear-off products such as nose stickers can remove blackheads, a large number of keratin cells will be peeled off during the tearing process, which can easily cause facial skin allergies and redness, and after mechanical tearing, the pores will become larger. Because mud masks have a large amount of active adsorbents, they can penetrate pores and deeply clean pores while achieving the cleaning of waste keratin. For example, mud masks disclosed in Chinese invention patents with application number CN202410521309.9 (publication number CN118526439A) and Chinese invention patents with application number CN202410501762.3 (publication number CN118058980A).
[0004] However, most mud masks on the market have the following problems:
[0005] (1) Most of them have only short-term effects and can only remove blackheads and dirt on the surface of the skin. They cannot completely remove blackheads deep inside the skin. The blackhead removal effect is poor, which leads to recurring blackhead problems.
[0006] (2) The application effect is poor. When applying evenly with force, the skin's stratum corneum may be damaged due to poor dispersion and excessive friction, thereby destroying the skin barrier and causing sensitive skin. In addition, it is difficult to apply evenly, whether by hand or with the help of tools such as a mask brush, and it is easy to dirty the hands, resulting in poor comfort when used.
[0007] (3) In order to carry kaolin, excessive polymer thickening materials are added. After facial application, as the water evaporates, the viscosity and shear force of the material itself increase, causing it to adhere to the skin surface and be difficult to clean. Summary of the invention
[0008] The first technical problem to be solved by the present invention is to provide a mud mask composition with good blackhead removing effect in view of the prior art.
[0009] The second technical problem to be solved by the present invention is to provide a mud mask composition which has good blackhead removing effect and is easy to clean in view of the prior art.
[0010] The third technical problem to be solved by the present invention is to provide a mud mask composition which has good blackhead removing effect and is easy to apply in view of the prior art.
[0011] The fourth technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned mud film composition in view of the prior art.
[0012] The technical solution adopted by the present invention to solve the above-mentioned first and second technical problems is: a mud film composition, characterized in that it includes phase A, phase B, phase C and phase D, and respectively includes the following components and their mass fractions:
[0013] Phase A:
[0014] 15-40 parts of purified water,
[0015] 10-30 parts of butanediol,
[0016] 0.1-1 part of potassium hydroxide;
[0017] Phase B:
[0018] 2 to 10 parts of polydimethylsiloxane,
[0019] 1-5 parts of stearic acid;
[0020] Phase C:
[0021] 5-20 parts of kaolin,
[0022] 2-10 portions of black charcoal cocoa powder,
[0023] Phase D:
[0024]
[0025] Furthermore, the phase C also includes a dispersant. By adding the dispersant, the mud film is prevented from agglomerating, and the mud film is easy to spread and disperse, so as to achieve the effect of uniform application and covering.
[0026] Furthermore, the dispersant includes titanium dioxide and fluorphlogopite. Fluorphlogopite can effectively reduce the friction between materials and between materials and skin due to its special layered structure, improve the dispersibility of mud film, and at the same time improve the skin feel of use, and reduce skin irritation (most of the existing mud films have problems such as redness and stinging of the skin after irritation), while TiO2 (titanium dioxide) can load metal ions in the mud film, thereby reducing the risk of mud film agglomeration and better improving the dispersibility of the mud film. In this way, the present invention combines titanium dioxide with fluorphlogopite as a dispersant, and the combination of the two is stable. Fluorphlogopite can reduce the irritation of TiO2 to the skin. The combination of the two can significantly improve the dispersibility of the mud film, and further ensure the uniform application and coverage of the mud film.
[0027] Preferably, the mass fraction of titanium dioxide in the dispersant is 3 to 15 parts, and the mass fraction of fluorphlogopite is 5 to 15 parts. While ensuring the dispersing effect of the dispersant, it can better reduce irritation to the skin and avoid the heavy feeling caused by excessive TiO2, which is conducive to improving the skin feel of the mud mask.
[0028] Further, the D phase also includes a film-forming agent. The mud film is a porous system, and water evaporates quickly under certain conditions. On the one hand, it will dry up the mud film and make it difficult to clean. On the other hand, it will cause the small molecule active substances dissolved in the water to volatilize and dissipate, and cannot effectively penetrate into the stratum corneum and dermis, seriously affecting the use effect of the mud film (this is also one of the reasons why the target effect of many commercially available products is inconsistent with the actual use effect). The present invention adds a film-forming agent, so that after the mud film is evenly applied and covered, a surface film structure can be formed, and the moisturizing effect of stearic acid (the moisturizing property of stearic acid is also conducive to the film-forming agent on the surface of the mud film) can be combined to effectively reduce water evaporation, thereby significantly reducing the loss of small molecule active substances, improving the bioavailability of small molecule active substances, achieving the target effect, and can form fixed closed vesicles inside the film, forming a pressure difference on the skin surface, increasing the material penetration effect, and further enhancing the biological activity of small molecule active substances.
[0029] Preferably, the film-forming agent is pullulan, and the mass fraction of the film-forming agent is 1 to 5 parts. Pullulan is a food film-forming agent. Compared with other common synthetic film-forming agents used in skin care products (for example, polyvinyl pyrrolidone / hexadecene copolymer, trimethylsiloxysilicate, acrylic resin and dimethylsiloxane copolymer, etc.), it is not only safer to use, so that the mud mask of the present application is more suitable for sensitive skin, but also has good moisturizing and biocompatibility, can form a one-way breathable film layer on the skin surface, improve the comfort of the mud mask, and because of its moisturizing properties, it can reduce the amount of stearic acid used. At the same time, with its good adhesion and stability, it can avoid the problem of excessive fluidity of the mud film caused by excessive stearic acid.
[0030] Furthermore, the D phase also includes zinc sulfate, and the mass fraction of the zinc sulfate is 1 to 5 parts. Although the present invention can achieve the effect of long-term shrinking pores through cinnamon bark extract, if the surface pores after dredging are not shrunk in time, they are easily blocked by accumulation of grease, dirt, etc. (especially problematic skin such as oily skin and acne skin). Therefore, the present invention adds zinc sulfate and uses zinc sulfate in the epidermis to achieve the effect of rapid pore astringency, while inhibiting IL inflammatory factors. In this way, the cooperation of zinc sulfate and cinnamon bark extract can achieve the pore repair effect of rapid pore shrinkage and long-term pore shrinkage, completely solve the problem of enlarged pores, and regain delicate skin.
[0031] The technical solution adopted to further solve the second technical problem is: a method for preparing the mud film composition as described above, characterized in that it comprises the following steps:
[0032] (1) Add purified water according to the above mass fractions into the container, stir and slowly add the remaining components of phase A at a stirring speed of 35 r / min to 40 r / min until all the remaining components of phase A are added;
[0033] (2) introducing steam into the above container and heating the liquid in the container to 85°C to 90°C, adding phase B according to the above mass fraction and stirring and dispersing at a stirring speed of 2500 r / min to 3000 r / min for 5 min to 10 min;
[0034] (3) Add phase C into the above container according to the above mass fractions, homogenize at 85°C to 90°C and -0.06 MPa or below for 10 to 15 minutes, and keep warm for 30 minutes;
[0035] (4) After standing for 10 minutes, cool down to 65°C-70°C, and add phase D into the above container according to the above mass fractions;
[0036] (5) After standing for 20 minutes, filter through a 100-mesh filter to obtain the desired material;
[0037] (6) The obtained material is cooled to 40°C to 55°C, packaged, naturally cooled to room temperature, and then sealed for storage.
[0038] The technical solution adopted to further solve the third technical problem mentioned above is: an application of the mud mask composition as described above in skin care products.
[0039] Compared with the prior art, the advantages of the present invention are:
[0040] Black and white heads are a type of keratin plug, which is a hardened colored grease blockage formed by excess oil secreted from the pores mixed with old waste keratin and blocked in the pores, and the oil is oxidized. First, supramolecular salicylic acid is made from salicylic acid and ethanol, glycerin and other substances through a specific process, which retains the advantages of salicylic acid and overcomes the disadvantages of salicylic acid. The supramolecular salicylic acid in the present invention utilizes its network molecular structure to allow its molecules to interact through hydrogen bonds and hydrophobic forces, making it easier to pass through the stratum corneum and cell membrane, and the penetration effect is significantly improved. Therefore, the present invention utilizes supramolecular salicylic acid to penetrate and dissolve keratin and dissolve keratin plugs, thereby obtaining a good black and white head dredging effect.
[0041] Next, the present invention combines PCA zinc with mahogany seed extract, wherein PCA zinc is used to inhibit 5α-reductase, thereby weakening signal stimulation to reduce oil production, inhibiting lipid peroxidation, and reducing lipid production in sebaceous glands in the early stage of oil synthesis. Mahogany seed extract is used to reduce serum-induced and IGF-1-induced lipid synthesis, so that the source of skin oil production can be controlled by combining PCA zinc and mahogany seed extract.
[0042] Secondly, quaternary ammonium salt-73 is generally used in the prior art, and its cationic properties are used to destroy bacterial cell membranes to achieve bactericidal and antibacterial effects. However, in the mud film system, the cations of quaternary ammonium salt-73 will be neutralized, resulting in a significant reduction in the antibacterial effect. Therefore, according to the system characteristics of the mud film composition, the present invention uses red pine leaf extract as a bactericidal and antibacterial component, and uses red pine leaf extract to inhibit the activity of Propionibacterium acnes, reduce the induced nitric oxide production, and reduce irritation. Since red pine leaf extract has no ionicity, its bactericidal and antibacterial properties will not be affected in the mud film composition system of the present invention.
[0043] Finally, shrinking pores in the dermis is the key to pore repair. The present invention uses cinnamon bark extract to promote the production of type III collagen and filaggrin in the basal layer to increase the thickness of the dermis, thereby achieving a long-lasting pore shrinking effect and completely solving the problem of blackheads.
[0044] As can be seen from the above, the present invention adopts four levels of pore dredging, source oil control, bacteriostasis and antibacterial, and pore repair in sequence according to the mechanism and characteristics of black and white head formation to systematically solve the black and white head problem of facial skin, avoid the recurrence of the black and white head problem, and completely solve the black and white head problem.
[0045] In addition, in existing mud mask products, excessive polymer thickening raw materials are added to carry kaolin, which easily leads to water loss and evaporation after use, thereby increasing the viscosity and shear force of the material itself, and adhering to the skin surface, making it difficult to clean. Therefore, the present invention selects stearic acid, uses natural fatty acid neutralization technology, and combines the moisturizing, dispersing and coagulation technology of polyol polyhydroxy structure to achieve cross-linking polymerization and coagulation molding, solving the problem of difficult cleaning.
[0046] In addition, in the preparation method of the present invention, a dispersant is added and stearic acid is used to improve the overall dispersibility of the mud film composition, thereby ensuring the uniformity of the dispersion of the mud film composition when it is discharged, avoiding damage to the filter screen, and ensuring uniform distribution of small molecular active substances in the finished product. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a comparison diagram of the area ratio of porphyrin oil before and after use in the embodiment of the present invention;
[0048] Figure 2 This is a comparison chart of the blackhead area ratio before and after use in an embodiment of the present invention;
[0049] Figure 3 This is a comparison chart of the pore area ratio before and after use in the embodiment of the present invention. DETAILED DESCRIPTION
[0050] The present invention is further described in detail below with reference to the accompanying drawings.
[0051] 1. Implementation
[0052] Embodiment 1:
[0053] A mud film composition, comprising phase A, phase B, phase C and phase D, and respectively comprising the following components and their mass fractions:
[0054] Phase A:
[0055] 15 parts of purified water, 10 parts of butanediol, 0.1 parts of potassium hydroxide;
[0056] Phase B:
[0057] 2 parts of polydimethylsiloxane, 1 part of stearic acid;
[0058] Phase C:
[0059] 5 parts of kaolin, 3 parts of titanium dioxide, 5 parts of fluorphlogopite, 2 parts of black charcoal cocoa powder;
[0060] Phase D:
[0061] 0.5 parts of cetyl ethylhexanoate, 0.5 parts of hydroxyacetophenone, 2 parts of sodium cocoyl glutamate, 2 parts of supramolecular salicylic acid, 0.1 parts of PCA zinc, 1 part of red pine leaf extract (manufacturer BASF, model Bix'Active, the same below), 1 part of cinnamon bark extract (manufacturer SETHIC model, oil control complex 315, the same below), 1 part of pullulan, and 1 part of zinc sulfate.
[0062] The mud film composition is prepared by the following steps:
[0063] (1) Add purified water according to the above mass fractions into a stirring pot, stir and slowly add the remaining components of phase A at a stirring speed of 35 r / min until all the remaining components of phase A are added;
[0064] (2) introducing steam into the stirring pot and heating the liquid in the stirring pot to 85° C., adding phase B according to the above mass fraction and stirring and dispersing at a stirring speed of 2500 r / min for 5 min;
[0065] (3) Add phase C according to the above mass fractions into the above stirring pot, homogenize at 85°C, -0.06MPa or below for 10 minutes, and keep warm for 30 minutes;
[0066] (4) After standing for 10 min, cool down to 65° C. and add phase D into the stirring pot according to the above mass fractions;
[0067] (5) After standing for 20 minutes, filter through a 100-mesh filter to obtain the desired material;
[0068] (6) After the obtained material is cooled to 40°C, it is packaged, naturally cooled to room temperature, and then sealed for storage.
[0069] Embodiment 2:
[0070] A mud film composition, comprising phase A, phase B, phase C and phase D, and respectively comprising the following components and their mass fractions:
[0071] Phase A:
[0072] 30 parts of purified water, 20 parts of butanediol, 0.5 parts of potassium hydroxide;
[0073] Phase B:
[0074] 6 parts of polydimethylsiloxane, 3 parts of stearic acid;
[0075] Phase C:
[0076] 12 parts of kaolin, 9 parts of titanium dioxide, 10 parts of fluorphlogopite, 6 parts of black charcoal cocoa powder;
[0077] Phase D:
[0078] 1.2 parts of cetyl ethylhexanoate, 1.2 parts of hydroxyacetophenone, 3.5 parts of sodium cocoyl glutamate, 3.5 parts of supramolecular salicylic acid, 0.3 parts of PCA zinc, 3 parts of mahogany seed extract, 3 parts of red pine leaf extract, 3 parts of cinnamon bark extract, 3 parts of pullulan, and 3 parts of zinc sulfate.
[0079] The mud film composition is prepared by the following steps:
[0080] (1) Add purified water according to the above mass fractions into a stirring pot, stir and slowly add the remaining components of phase A at a stirring speed of 35 r / min until all the remaining components of phase A are added;
[0081] (2) introducing steam into the stirring pot and heating the liquid in the stirring pot to 90° C., adding phase B according to the above mass fraction and stirring and dispersing at a stirring speed of 3000 r / min for 5 min;
[0082] (3) Add phase C according to the above mass fractions into the above stirring pot, homogenize at 90°C, -0.06MPa or below for 15 minutes, and keep warm for 30 minutes;
[0083] (4) After standing for 10 min, cool down to 70° C. and add phase D into the stirring pot according to the above mass fractions;
[0084] (5) After standing for 20 minutes, filter through a 100-mesh filter to obtain the desired material;
[0085] (6) After the obtained material is cooled to 55°C, it is packaged, naturally cooled to room temperature, and then sealed for storage.
[0086] Embodiment 3:
[0087] A mud film composition, comprising phase A, phase B, phase C and phase D, and respectively comprising the following components and their mass fractions:
[0088] Phase A:
[0089] 40 parts of purified water, 30 parts of butanediol, 1 part of potassium hydroxide;
[0090] Phase B:
[0091] 10 parts of polydimethylsiloxane, 5 parts of stearic acid;
[0092] Phase C:
[0093] 20 parts of kaolin, 15 parts of titanium dioxide, 15 parts of fluorphlogopite, 10 parts of black charcoal cocoa powder;
[0094] Phase D:
[0095] 2 parts of cetyl ethylhexanoate, 2 parts of hydroxyacetophenone, 5 parts of sodium cocoyl glutamate, 5 parts of supramolecular salicylic acid, 0.5 parts of PCA zinc, 5 parts of mahogany seed extract, 5 parts of red pine leaf extract, 5 parts of cinnamon bark extract, 5 parts of pullulan, and 5 parts of zinc sulfate.
[0096] The mud film composition is prepared by the following steps:
[0097] (1) Add purified water according to the above mass fractions into a stirring pot, stir and slowly add the remaining components of phase A at a stirring speed of 40 r / min until all the remaining components of phase A are added;
[0098] (2) introducing steam into the stirring pot and heating the liquid in the stirring pot to 90° C., adding phase B according to the above mass fraction and stirring and dispersing at a stirring speed of 3000 r / min for 10 min;
[0099] (3) Add phase C according to the above mass fractions into the above stirring pot, homogenize at 90°C, -0.06MPa or below for 10 to 15 minutes, and keep warm for 30 minutes;
[0100] (4) After standing for 10 min, cool down to 70° C. and add phase D into the stirring pot according to the above mass fractions;
[0101] (5) After standing for 20 minutes, filter through a 100-mesh filter to obtain the desired material;
[0102] (6) After the obtained material is cooled to 55°C, it is packaged, naturally cooled to room temperature, and then sealed for storage.
[0103] 2. Comparative Examples
[0104] Comparative Example 1:
[0105] Except that phase C does not contain a dispersant, other components and their mass fractions are the same as those in Example 1, and the preparation method is also the same as that in Example 1.
[0106] Comparative Example 2:
[0107] Except that phase D does not contain a film-forming agent, other components and their mass fractions are the same as those in Example 1, and the preparation method is also the same as that in Example 1.
[0108] Comparative Example 3:
[0109] Except that phase D does not contain zinc sulfate, other components and their mass fractions are the same as those in Example 1, and the preparation method is also the same as that in Example 1.
[0110] 3. Comparative Example:
[0111] Commercially available mud mask (GA mud mask).
[0112] 4. Blackhead removal test
[0113] 1. Test samples
[0114] Test objects: the mud mask compositions in each example and each comparative example, and a commercially available mud mask (GA mud mask).
[0115] Control: before and after use;
[0116] How to use: ① After cleaning your face, rotate out a proper amount of the paste, remove the protective cover, and apply a proper amount of the paste on your face, avoiding the area around the eyes and lips; ② Leave it on for 5-10 minutes, rinse with clean water and then proceed with your daily skin care.
[0117] Test area: cheeks, nose tip.
[0118] 2. Test Purpose
[0119] At least 30 subjects who met the criteria were recruited, and the test products were used to evaluate the cosmetics' effects on acne removal, exfoliation, oil control, improvement of skin smoothness, moisturizing, pore reduction, and improvement of skin roughness through instrument testing and image analysis.
[0120] All enrolled subjects met the following inclusion and exclusion criteria:
[0121] 2.1 Inclusion criteria:
[0122] 2.1.1 Healthy women / men, aged between 18 and 40 years old;
[0123] 2.1.2 People with oily facial skin (volunteers with forehead sebum exceeding 120 μg / cm2 within 8 hours);
[0124] 2.1.3 Be able to cooperate well with the experimenter and maintain a regular life during the study;
[0125] 2.1.4 Be able to read and understand all the contents of the informed consent form and voluntarily sign the informed consent form;
[0126] 2.1.5 During the trial, you agree not to use any cosmetics, drugs or health products that may affect the results.
[0127] 2.2 Exclusion criteria:
[0128] 2.2.1 Those who have used preparations that affect sebum secretion in the past month;
[0129] 2.2.2 Those who have used antihistamines in the past week or immunosuppressants in the past month;
[0130] 2.2.3 Those who have used any anti-inflammatory drugs in the test area within the past two months;
[0131] 2.2.4 Subjects with inflammatory skin diseases that have not been clinically cured;
[0132] 2.2.5 Patients with insulin-dependent diabetes mellitus;
[0133] 2.2.6 Patients who are receiving treatment for asthma or other chronic respiratory diseases;
[0134] 2.2.7 Those who have received anti-cancer chemotherapy in the past 6 months;
[0135] 2.2.8 Patients with immunodeficiency or autoimmune diseases;
[0136] 2.2.9 Women who are breastfeeding or pregnant;
[0137] 2.2.10 Bilateral mastectomy and bilateral axillary lymph node removal;
[0138] 2.2.11 The judges whose test results are affected by scars, pigmentation, atrophy, port wine stains, uneven skin color, folliculitis or other blemishes on the skin to be tested;
[0139] 2.2.12 Researchers currently participating in other clinical trials;
[0140] 2.2.13 People with highly sensitive constitutions;
[0141] 2.2.14 Non-voluntary participants or those who are unable to complete the required content according to the test requirements.
[0142] 3. Test method basis
[0143] Method: Instrumental analysis, image analysis
[0144] 4. Test equipment
[0145] Skin elasticity tester MPA580 (Colorimeter probe, Corneometer probe), skin surface texture analysis system Visioscan VC20plus, facial image camera system VISIA-CR, analytical balance.
[0146] 5. Test indicators (as shown in Table 1)
[0147] Table 1 Efficacy test
[0148]
[0149] 6. Statistics
[0150] Statistical analysis software was used for statistical analysis of the data.
[0151] Measurement data are expressed as mean ± standard deviation, and normal distribution test is performed. If the data meet the normal distribution requirements, the paired t test is used for comparison before and after the data, otherwise the two related sample rank sum test is used; the comparison of the rank data before and after the use of the two related sample rank sum test is used; the comparison between the test product and the control group is performed by the independent sample t test or rank sum test. The above statistical analysis is a two-tailed test, and the significance level is α = 0.05.
[0152] 7. Result determination
[0153] If the change results of any parameter in the relevant parameters at any visit time point before and after the use of the test sample on the experimental side are significantly different (P<0.05), the test sample is considered to have the corresponding efficacy, otherwise it is considered that the test sample has no corresponding efficacy.
[0154] 8. Test results
[0155] 8.1 Porphyrin oil area ratio
[0156] Table 2 Data of porphyrin oil area ratio at different time points (mean ± standard deviation) Unit: %
[0157] Group Before use (D0) After use (D28) Example 1 4.89±1.39 3.12±1.89 Example 2 4.71±1.22 2.76±1.56 Example 3 4.93±2.08 2.45±1.32 Comparative Example 1 4.81±1.56 3.17±1.80 Comparative Example 2 4.78±1.68 3.45±1.22 Comparative Example 3 4.87±1.59 3.77±1.49 Comparative Example 4.71±2.01 4.26±2.13
[0158] Table 3 Change rate of porphyrin oil area ratio
[0159] Group After use (D28) Example 1 -36.20% Example 2 -41.40% Example 3 -50.30% Comparative Example 1 -34.10% Comparative Example 2 -27.82% Comparative Example 3 -22.59% Comparative Example -9.55%
[0160] Table 4 Test results of porphyrin oil area ratio
[0161] Time Comparison N Statistical methods p-value Significance Example 1 (D28) Compared with before use 30 Paired t-test 0.0000 *** Example 2 (D28) Compared with before use 30 Paired t-test 0.0000 *** Example 3 (D28) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 1 (D28) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 2 (D28) Compared with before use 30 Paired t-test 0.002 ** Comparative Example 3 (D28) Compared with before use 30 Paired t-test 0.003 ** Comparative Example (D28) Compared with before use 30 Paired t-test 0.03 *
[0162] Significance marking method: "ns" indicates no statistical difference, P>0.05; "*" indicates significant difference, 0.01≤P<0.05; "**" indicates very significant difference, 0.001≤P<0.01; "***" indicates extremely significant difference, P<0.001. "N" indicates the number of users = 30.
[0163] The test results of porphyrin oil area ratio are shown in Table 2, Table 3, Table 4 and Figure 1 As shown, among which, Figure 1It can be seen that after using the mud mask (Example 1) of the present invention for 28 consecutive days, the porphyrin oil area ratio of the test sample area of the subject was significantly different from the basal value, decreasing by 36.20%, and the change rate was much greater than the 9.55% of the ordinary commercially available mud mask. In addition, the change rate of the porphyrin oil area ratio of Examples 2 and 3 increased linearly, reaching 41.40% and 50.30%. The change rate of Comparative Example 1 was 34.10%, while in Comparative Example 2, the film-forming agent was lacking, the permeability of the active substance decreased, and the change rate of the porphyrin oil area ratio also decreased to 27.82%. In Comparative Example 3, zinc sulfate was lacking, which directly affected the oil production rate of the skin, and the change rate of the porphyrin oil area ratio continued to decrease to 22.59%.
[0164] 8.2 Blackhead area ratio
[0165] Table 5 Data of blackhead area ratio at different time points (mean ± standard deviation) Unit: %
[0166] Group Before use (D0) After use (D28) Example 1 28.67±2.31 17.30±2.99 Example 2 27.78±2.13 13.23±2.37 Example 3 29.24±3.01 11.38±2.84 Comparative Example 1 27.74±2.34 23.39±2.52 Comparative Example 2 28.11±2.77 21.89±3.09 Comparative Example 3 29.37±2.11 23.81±3.22 Comparative Example 29.19±3.15 24.66±3.14
[0167] Table 6 Change rate of blackhead area ratio
[0168] Group After use (D28) Example 1 -39.66% Example 2 -52.38% Example 3 -61.08% Comparative Example 1 -15.68% Comparative Example 2 -22.13% Comparative Example 3 -11.71% Comparative Example -15.52%
[0169] Table 7 Blackhead area ratio test results
[0170] Time Comparison N Statistical methods p-value Significance Example 1 (D28) Compared with before use 30 Paired t-test 0.0000 *** Example 2 (D28) Compared with before use 30 Paired t-test 0.0000 *** Example 3 (D28) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 1 (D28) Compared with before use 30 Paired t-test 0.04 * Comparative Example 2 (D28) Compared with before use 30 Paired t-test 0.02 * Comparative Example 3 (D28) Compared with before use 30 Paired t-test 0.04 * Comparative Example (D28) Compared with before use 30 Paired t-test 0.04 *
[0171] Significance marking method: "ns" indicates no statistical difference, P>0.05; "*" indicates significant difference, 0.01≤P<0.05; "**" indicates very significant difference, 0.001≤P<0.01; "***" indicates extremely significant difference, P<0.001. "N" indicates the number of users = 30.
[0172] The results of the blackhead area ratio are shown in Tables 5, 6 and 7. The comparison chart of the effective improvement of the blackhead area ratio (mud mask in Example 1) is as follows: Figure 2 As shown. Figure 2It can be seen that after using the mud mask (Example 1) of the present invention for 28 days continuously, the blackhead area ratio of the test sample area of the subject has a very significant difference compared with the basic value, which is reduced by 39.66%, and the change rate is much greater than the 15.52% of the ordinary commercially available mud mask. In addition, the change rate of the blackhead area ratio of Example 2 and Example 3 increases linearly, reaching 52.38% and 61.08%. Comparative Example 1 lacks a dispersant, and the material body cannot be evenly coated on the surface, which reduces the blackhead removal area, and its change rate decreases to 15.68%. Comparative Example 2 lacks a film-forming agent, the permeability of the active substance decreases, and the change rate of the blackhead area ratio also decreases to 22.13%. Comparative Example 3 lacks zinc sulfate, which directly affects the oil production rate of the skin, and the change rate of the increased oxidation blackhead area ratio continues to decrease, which is 11.71%.
[0173] 8.3 Scale exfoliation index results
[0174] Table 8 Data of scaling index at different time points (mean ± standard deviation) Unit: %
[0175] Group Before use (D0) After use (D28) Example 1 30.55±3.85 15.38±2.90 Example 2 31.36±2.87 12.34±2.38 Example 3 32.48±2.98 10.97±2.42 Comparative Example 1 30.32±3.12 17.30±2.89 Comparative Example 2 31.67±2.90 16.32±2.31 Comparative Example 3 32.92±2.33 17.23±2.15 Comparative Example 31.22±2.81 25.75±2.11
[0176] Table 9 Change rate of scaling index
[0177] Group After use (D28) Example 1 -49.66% Example 2 -60.65% Example 3 -66.23% Comparative Example 1 -42.94% Comparative Example 2 -48.47% Comparative Example 3 -47.66% Comparative Example -17.52%
[0178] Table 10 Scale peeling index test results
[0179] Time Comparison N Statistical methods p-value Significance Example 1 (D28) Compared with before use 30 Paired t-test 0.0000 *** Example 2 (D28) Compared with before use 30 Paired t-test 0.0000 *** Example 3 (D28) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 1 (D28) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 2 (D28) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 3 (D28) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example (D28) Compared with before use 30 Paired t-test 0.04 *
[0180] Significance marking method: "ns" indicates no statistical difference, P>0.05; "*" indicates significant difference, 0.01≤P<0.05; "**" indicates very significant difference, 0.001≤P<0.01; "***" indicates extremely significant difference, P<0.001. "N" indicates the number of users = 30.
[0181] The results of the scaling exfoliation index test are shown in Tables 8, 9 and 10. It can be seen from the data shown in Tables 8, 9 and 10 that after using the mud mask in Example 1 of the present invention for 28 days, the scaling exfoliation index of the test sample area of the subject has a very significant difference compared with the basic value, which is reduced by 49.66%, and the change rate is much greater than 17.52% of the ordinary commercially available mud mask. In addition, the scaling exfoliation index change rate of Example 2 and Example 3 increases linearly, reaching 60.65% and 66.23%. Comparative Example 1 lacks a dispersant, and the material body cannot be evenly coated on the surface, which reduces the scaling exfoliation index, and its change rate drops to 42.94%. Comparative Example 2 lacks a film-forming agent, and the water content of the stratum corneum is lost faster, and the scaling exfoliation index change rate also drops to 48.47%. Comparative Example 3 lacks zinc sulfate, which affects the exfoliation effect of the skin stratum corneum, and the change rate continues to decrease to 47.66%.
[0182] 8.4 Pore area ratio
[0183] Table 11 Data of pore area ratio at different time points (mean ± standard deviation) Unit: %
[0184] Group Before use (D0) After use (D28) Example 1 1.09±0.32 0.53±0.29 Example 2 1.16±0.23 0.43±0.12 Example 3 1.20±0.16 0.38±0.11 Comparative Example 1 1.12±0.21 0.62±0.10 Comparative Example 2 1.23±0.19 0.79±0.14 Comparative Example 3 1.21±0.11 0.98±0.16 Comparative Example 1.08±0.41 0.89±0.31
[0185] Table 12 Change rate of pore area ratio
[0186] Group After use (D28) Example 1 -51.38% Example 2 -62.93% Example 3 -68.33% Comparative Example 1 -44.64% Comparative Example 2 -35.77% Comparative Example 3 -19.01% Comparative Example -17.59%
[0187] Table 13 Pore area ratio test results
[0188] Time Comparison N Statistical methods p-value Significance Example 1 (D28) Compared with before use 30 Paired t-test 0.0000 *** Example 2 (D28) Compared with before use 30 Paired t-test 0.0000 *** Example 3 (D28) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 1 (D28) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 2 (D28) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 3 (D28) Compared with before use 30 Paired t-test 0.03 * Comparative Example (D28) Compared with before use 30 Paired t-test 0.04 *
[0189] Significance marking method: "ns" indicates no statistical difference, P>0.05; "*" indicates significant difference, 0.01≤P<0.05; "**" indicates very significant difference, 0.001≤P<0.01; "***" indicates extremely significant difference, P<0.001. "N" indicates the number of users = 30.
[0190] The test results of pore area ratio are shown in Table 11, Table 12, Table 13 and Figure 3 (mud film in Example 1) as shown in Table 11, Table 12, Table 13 and Figure 3It can be seen that after using the mud mask (Example 1) of the present invention for 28 days continuously, the pore area ratio of the test sample area of the subject has a very significant difference compared with the basic value, which is reduced by 51.38%, and the change rate is much greater than the 17.59% of the ordinary commercially available mud mask. In addition, the change rate of the pore area ratio of Examples 2 and 3 increases linearly, reaching 62.93% and 68.33%. Comparative Example 1 lacks a dispersant, and the material body cannot be evenly coated on the surface, which reduces the pore removal area, and its change rate decreases to 44.64%. Comparative Example 2 lacks a film-forming agent, the permeability of the active substance decreases, and the immediate mechanical pulling force decreases, and the change rate of the pore area ratio also decreases to 35.77%. Comparative Example 3 lacks zinc sulfate, which directly affects the oil production rate of the skin, increases oil, and expands the pore area ratio. The change rate continues to decrease to 19.01%.
[0191] V. Cosmetic coating performance test
[0192] The test samples used solid-state cross-linking technology, which significantly improved the coating performance of the mud film, shortened the application time, and avoided local cracking of the mud film material due to uneven application, which could damage the skin and greatly enhanced the ease of use.
[0193] This trial design uses the subjects' own before and after control, reduces or controls bias through randomization and double-blind methods, and collects product use feedback information from the subjects through questionnaire surveys. The subjects are asked to use the test products directly according to the usage characteristics and methods indicated on the cosmetic product labels. After 28 days of use, the feelings after using the products are scored. The evaluation indicators of the trial are as follows:
[0194] question Very dissatisfied Dissatisfied generally satisfy Very satisfied The sample is evenly applied to the skin quickly 1 2 3 4 5
[0195] Evaluation of product experience after use: Statistical analysis software was used to perform statistical analysis of the data. The subjects evaluated the usability of the product at each test time point after using the product, and the percentage of people who gave positive evaluations (4-5 points) in each indicator was calculated in percentage form. A binomial test was used to test the significance of the percentages of those who chose satisfaction (4-5 points) and those who did not choose satisfaction (1-3 points), with a significance level of α = 0.05. The results are shown in Table 14.
[0196] Table 14 Self-assessment results and statistical analysis results
[0197]
[0198] Note: The subjects evaluated the usability of the product for 28 days and the percentage of the number of people who gave positive evaluation (4-5 points) in each indicator was calculated. The number of people counted was 30.
[0199] Significance marking method: "ns" indicates no statistical difference, P>0.05; "*" indicates significant difference, 0.01≤P<0.05; "**" indicates very significant difference, 0.001≤P<0.01; "***" indicates extremely significant difference, P<0.001. The test method is binomial test, and the number of statistical data is 30 people. VI. Mildness test
[0200] Most of the mud masks on the market contain adhesives and acids, which may cause skin irritation, redness, swelling or dryness, especially for sensitive skin. Frequent use may cause pore dilation or damage the pore wall, which will aggravate the blackhead problem. Therefore, while effectively solving the blackhead problem, it is also necessary to ensure the safety of the product. The human patch test is used to verify that the product is safe and non-irritating and suitable for sensitive skin.
[0201] 1. Lactic acid stinging test
[0202] Experimental method: Drop 50 μl of 10% lactic acid on a single-layer filter paper with a diameter of 0.8 cm, and place it on the nasolabial groove of the subject. Ask the subject about the tingling sensation at 2.5 minutes and 5 minutes respectively, and observe the skin reaction. Score from 0 to 3 points according to no, mild, moderate, and severe tingling. Subjects with a total score of ≥ 3 points in the lactic acid tingling test can be selected as sensitive skin subjects.
[0203] Table 15 Data of lactic acid stinging scores at different time points (mean ± standard deviation)
[0204] Group Before use (D0) After use (8h) After use (D28) Example 1 3.67±0.23 2.32±0.32 1.83±0.18 Example 2 3.74±0.13 2.34±0.31 1.78±0.11 Example 3 3.86±0.23 2.42±0.17 1.57±0.13 Comparative Example 1 3.62±0.33 2.35±0.27 1.87±0.16 Comparative Example 2 3.54±0.27 2.41±0.25 1.87±0.21 Comparative Example 3 3.89±0.26 2.73±0.34 1.99±0.12 Comparative Example 3.59±0.32 2.97±0.47 2.45±0.25
[0205] Table 16 Lactic acid stinging score change rate
[0206] Group After use (8h) After use (D28) Example 1 -36.78% -50.14% Example 2 -37.43% -52.41% Example 3 -37.31% -59.33% Comparative Example 1 -35.08% -48.34% Comparative Example 2 -31.92% -47.18% Comparative Example 3 -29.82% -48.84% Comparative Example -17.27% -31.75%
[0207] Table 17 Lactic acid stinging score test results
[0208] Time Comparison N Statistical methods p-value Significance Example 1 (D28) Compared with before use 30 Paired t-test 0.0000 *** Example 1 (8h) Compared with before use 30 Paired t-test 0.0000 *** Example 2 (D28) Compared with before use 30 Paired t-test 0.0000 *** Example 2 (8h) Compared with before use 30 Paired t-test 0.0000 *** Example 3 (D28) Compared with before use 30 Paired t-test 0.0000 *** Example 3 (8h) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 1 (D28) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 1 (8h) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 2 (D28) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 2 (8h) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 3 (D28) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example 3 (8h) Compared with before use 30 Paired t-test 0.0000 *** Comparative Example (8h) Compared with before use 30 Paired t-test 0.04 * Comparative Example (D28) Compared with before use 30 Paired t-test 0.03 *
[0209] Significance marking method: "ns" indicates no statistical difference, P>0.05; "*" indicates significant difference, 0.01≤P<0.05; "**" indicates very significant difference, 0.001≤P<0.01; "***" indicates extremely significant difference, P<0.001. "N" indicates the number of users = 30.
[0210] The results of the lactic acid stinging test are shown in Tables 15, 16 and 17. It can be seen from Tables 15, 16 and 17 that after using the mud mask of the present invention (Example 1) for 8 hours, the lactic acid stinging score of the test sample area of the subject has a very significant difference compared with the baseline value, which is reduced by 36.78%, and the change rate is much greater than 17.27% of the ordinary commercially available mud mask. In addition, the change rate of the lactic acid stinging score of Example 2 and Example 3 increases linearly, reaching 37.43% and 37.31%. Comparative Example 1 lacks a dispersant, and the material body cannot be evenly coated on the surface, and its change rate decreases to 35.08%, while Comparative Example 2 lacks a film-forming agent, the permeability of the active substance decreases, and the change rate of the lactic acid stinging score also decreases to 31.92%, while Comparative Example 3 lacks zinc sulfate, which directly affects the oil production rate of the skin, increases triglycerides, and increases the activity of Propionibacterium acnes, and the change rate of the lactic acid stinging score continues to decrease, which is 29.82%.
[0211] After using the mud mask of the present invention (Example 1) for 28 days, the lactic acid stinging score of the test sample area of the subject was significantly different from the baseline value, decreasing by 50.14%, and the change rate was much greater than 31.75% of the ordinary commercially available mud mask. In addition, the change rate of the lactic acid stinging score of Example 2 and Example 3 increased linearly, reaching 52.41% and 59.33%. Comparative Example 1 lacked a dispersant, and the material body could not be evenly coated on the surface, and its change rate decreased to 48.34%. Comparative Example 2 lacked a film-forming agent, the permeability of the active substance decreased, and the change rate of the lactic acid stinging score also decreased to 47.18%. Comparative Example 3 lacked zinc sulfate, which directly affected the oil production rate of the skin, increased triglycerides, and increased the activity of Propionibacterium acnes, and the change rate of the lactic acid stinging score continued to decrease to 48.84%.
[0212] 2. Human skin patch test:
[0213] Skin occlusion patch test (sensitive skin) Materials and methods
[0214] 2.1 Test substance: Dilute the final product with distilled water to a concentration of 5%.
[0215] 2.2 Negative control: the above test substance excipient control.
[0216] 2.3 Subjects: A total of 30 subjects, including 10 males and 20 females, aged 20 to 43 years old, with an average age of 30.40±6.11 years old, met the voluntary inclusion criteria.
[0217] 2.3.1 Inclusion criteria
[0218] Positive lactate sting screen result:
[0219] 50 μL of 10% lactic acid solution was applied to the nasolabial groove and any cheek, and the subjects were asked about their subjective symptoms at 2.5 minutes and 5 minutes, respectively, and scored according to a 4-point system (0 for no tingling, 1 for mild tingling, 2 for moderate tingling, and 3 for severe tingling). The two scores were then added together, and those with a total score of ≥3 were considered to have a positive lactic acid tingling reaction.
[0220] 2.3.2 Exclusion criteria
[0221] 2.3.2.1 Those who have used preparations that affect sebum secretion in the past month;
[0222] 2.3.2.2 Those who have used antihistamines in the past week or immunosuppressants in the past month;
[0223] 2.3.2.3 Those who have used any anti-inflammatory drugs in the test area within the past two months;
[0224] 2.3.2.4 Subjects suffering from inflammatory skin diseases that have not been clinically cured;
[0225] 2.3.2.5 Patients with insulin-dependent diabetes mellitus;
[0226] 2.3.2.6 Patients who are receiving treatment for asthma or other chronic respiratory diseases;
[0227] 2.3.2.7 Those who have received anti-cancer chemotherapy in the past 6 months;
[0228] 2.3.2.8 Patients with immunodeficiency or autoimmune diseases;
[0229] 2.3.2.9 Women who are breastfeeding or pregnant;
[0230] 2.3.2.10 Bilateral mastectomy and bilateral axillary lymph node removal;
[0231] 2.3.2.11 The judges whose test results are affected by scars, pigmentation, atrophy, port wine stains, uneven skin color, folliculitis or other blemishes on the skin to be tested;
[0232] 2.3.2.12 Researchers currently participating in other clinical trials;
[0233] 2.3.2.13 People with highly sensitive constitutions;
[0234] 2.4 Spot test method:
[0235] Select qualified patch test equipment and use the closed patch test method. Place about 0.020mL to 0.025mL of the test substance in the patch tester and apply it to the back of the subject with a low-allergenic tape. Remove the test substance after 24 hours and observe the skin reaction 0.5, 24, and 48 hours after removal. Record the results according to Table 1 on page 542 of the "Technical Specification for Safety of Cosmetics" (2015 edition). The results are shown in Table 18.
[0236] Table 18 Summary of human skin patch test (sensitive skin) results
[0237]
[0238] The human skin patch test results in Table 18 show that among the 30 sensitive skin subjects in the Example group, 0 cases had grade 1 adverse reactions, 0 cases had grade 2 adverse reactions, 0 cases had grade 3 adverse reactions, and 0 cases had grade 4 adverse reactions. The results of the Comparative Example group were the same as those of the Example group, while in the Control group, 3 cases had grade 1 adverse reactions and 1 case had grade 2 adverse reactions at 0.5h, 2 cases had grade 1 adverse reactions at 24h, and 2 cases had grade 1 adverse reactions at 48h.
Claims
1. A mud film composition, characterized in that: It includes phase A, phase B, phase C and phase D, and respectively includes the following components and their mass fractions: Phase A: 15-40 parts of purified water, 10-30 parts of butanediol, 0.1-1 part of potassium hydroxide; Phase B: 2 to 10 parts of polydimethylsiloxane, 1-5 parts of stearic acid; Phase C: 5-20 parts of kaolin, 2-10 portions of black charcoal cocoa powder, Phase D:
2. The mud film composition according to claim 1, characterized in that: The phase C also includes a dispersant.
3. The mud film composition according to claim 2, characterized in that: The dispersant includes titanium dioxide and fluorphlogopite.
4. The mud film composition according to claim 3, characterized in that: The mass fraction of titanium dioxide in the dispersant is 3 to 15 parts, and the mass fraction of fluorphlogopite is 5 to 15 parts.
5. The mud film composition according to any one of claims 1 to 4, characterized in that: The phase D also includes a film former.
6. The mud film composition according to claim 6, characterized in that: The film-forming agent is pullulan, and the mass fraction of the film-forming agent is 1 to 5 parts.
7. The mud film composition according to claim 5, characterized in that: The D phase also includes zinc sulfate, and the mass fraction of the zinc sulfate is 1 to 5 parts.
8. A method for preparing the mud film composition according to any one of claims 1 to 7, characterized in that The following steps are involved: (1) Add purified water according to the above mass fractions into the container, stir and slowly add the remaining components of phase A at a stirring speed of 35 r / min to 40 r / min until all the remaining components of phase A are added; (2) introducing steam into the above container and heating the liquid in the container to 85°C to 90°C, adding phase B according to the above mass fraction and stirring and dispersing at a stirring speed of 2500-3000 r / min for 5 to 10 min; (3) Add phase C into the above container according to the above mass fractions, homogenize at 85°C to 90°C and -0.06 MPa or below for 10 to 15 minutes, and keep warm for 30 minutes; (4) After standing for 10 minutes, cool down to 65°C-70°C, and add phase D into the above container according to the above mass fractions; (5) After standing for 20 minutes, filter through a 100-mesh filter to obtain the desired material; (6) The obtained material is cooled to 40°C to 55°C, packaged, naturally cooled to room temperature, and then sealed for storage.
Citation Information
Patent Citations
Oil control and acne removal composition and application thereof
CN107126379A
Activated carbon mud mask and preparation method thereof
CN111870548A
Skin mud mask capable of converging, repairing and adsorbing grease and preparation process of skin mud mask
CN115006268A
Oil-control soothing skin-care composition and cosmetic, preparation method therefor, and use thereof
WO2024032447A1